D8 Ülkeleri Arasındaki Dış Ticaret İşlemlerinde Barter Yönteminin Uygulanabilirliği / Applicability of Barter Method in Foreign Trade Transactions between D-8 Countries - Aksu, Murat; Gürbüz, Ahmet (Journal of History Culture and Art Research, 2017)
Abstract Economic crises, which are experienced every 10 years, increase the obligation to use alternative methods in foreign trade. One of the main ideas advocated by governments to develop the economy is to encourage local expenditures. However, it is not clear how this policy will motivate behavior change. Although local currency initiatives are becoming increasingly popular, some practicalities are seldom successful in promoting long-term spending on expenditure behaviors. It is important to develop the (BARTER) system to overcome some limitations of local currencies. Barter system is seen as an important source of funding for foreign trade in context of many countries. Given the rising of cost due to crises and the volatility of local currency value, the barter system is an effective way to reduce costs, improve business efficiency and free up stocks. It is of great importance for countries to keep good relations with their relative states. Similarity in race, religion or tradition allows the world system to establish a common understanding. The D-8 organization established for this purpose appears as one unit of dynamic and young population from lands of three continents. However, despite this potential, the D-8 countries are having trouble on getting into action exactly. Present research sought to analyze how Turkey can improve foreign trade with D-8 countries by using barter system and how to supply products and product groups with money substitutes. Öz Yaklaşık her on yılda bir yaşanan ekonomik krizler, dış ticarette alternatif yöntemler kullanma mecburiyetini artırmaktadır. Hükümetlerin savunduğu temel fikirlerden biri, yerel harcamaları teşvik ederek büyümeyi sağlamaktır. Ancak bu durumun davranışsal değişimi nasıl motive edeceği açık değildir. Yerel para birimi girişimleri gittikçe daha popüler olmasına rağmen, bazı pratiklikler harcama davranışlarında uzun vadede ve yaygınlaşmanın teşvik edilmesinde nadiren başarılıdır. Yerel para birimlerinin bazı sınırlamalarını aşmak için, Barter sisteminin geliştirilmesi önemlidir. Barter sistemi ülkeler açısından dış ticarette önemli bir finansman kaynağı olarak görülmektedir. Krizler ve yerel para değerinin oynaklığı nedeniyle artan maliyet unsuru göz önüne alınırsa Barter sistemi maliyeti düşürmenin, ticari etkinliği artırmanın ve stokları eritmenin etkili bir yoludur. Akraba devletler ile ilişkide olmak ülkeler açısından büyük önem arz eder. Irk, din veya geleneklerde benzerlik dünya sisteminde ortak bir anlayış oluşturmasını sağlar. Bu amaçlarla kurulmuş olan D-8 teşkilatı, üç kıtada toprak sahibi, dinamik ve genç nüfusu olan bir birlik olarak gözükmektedir. Ancak bu potansiyele rağmen, D-8 ülkeleri tam anlamıyla harekete geçmek konusunda sıkıntı yaşamaktadır. Bu çalışmada, Türkiye’nin, Barter sistemini kullanarak D-8 ülkeleri ile olan dış ticaretini ne ölçüde geliştirebileceği ve ihtiyacı olan ürünleri ve ürün gruplarını para ikameleriyle nasıl temin edebileceği araştırılmıştır.